DIKSI DAN GAYA BAHASA PADA CERPEN ‘ANAK INI MAU MENGENCINGI JAKARTA?’ DAN RELEVANSINYA DENGAN MATERI AJAR DI SMA - Alif Fatin Febriani; Ani Rakhmawati; Atikah Anindyarini (Universitas Sebelas Maret, 2019)
ABSTRACT: The purpose of this study is to describe the diction, figure of speech and the relevance of Antologi Cerpen Pilihan Kompas 2015 ‘Anak Ini Mau Mengencingi Jakarta?’ And It’s Relevance to the Teaching Materials of Grade XI of Senior High School in the Curriculum of 2013. This research is a descriptive qualitative shaped with describe or illustrate the problems occurred and analyze the data in the form of words or sentences. Sampling techniques using is purposive sampling method. Engineering data collection using the technique of the analysis of the documents and interviews with informan. The validity used is sources and theory triangulation. Data analysis technique used is flow model of analysis. Procedure research conducted several different stages namely the preparation phase, the phase of implementation, and the stage of the preparation of the report. The results of these studies were found (1) utilization of diction with a total of 238 overall data; (2 the form of language stylistics with a total of 148 overall data; and (3) the relevance of Antologi Cerpen Pilihan Kompas 2015 Anak Ini Mau Mengencingi Jakarta? And It’s Relevance to the Bahasa Indonesia’s Teaching Materials of Grade XI of Senior High School in the Curriculum of 2013.